Answer:
119
Step-by-step explanation:
Answer:
the answer is 28
Step-by-step explanation:
i guessed ngl
Answer:
(-2,-2) and (-7,1)
Step-by-step explanation:
I can't see i am trying
Answer:
(2, -1)
Step-by-step explanation:
We can add the first equation by the second
(4x + 6y = 2)+(-4x + 4y = -12)=
10y=-10
we divide both sides by 10 to get
y=-1
We plug -1 in the second equation to get:
-4x+4(-1)=-12
-4x-4=-12
-4x=-8
Now, we divide both sides by -4
x=2
Hope this helps!
Answer: 60
Step-by-step explanation: